Arthroscopic Fragment Resection for Capitellar Osteochondritis Dissecans in Adolescent Athletes: 5- to 12-Year Follow-up. Issue 12 (12th December 2017) - Ueda, Yusuke; Sugaya, Hiroyuki; Takahashi, Norimasa; Matsuki, Keisuke; Tokai, Morihito; Onishi, Kazutomo; Hoshika, Shota; Hamada, Hiroshige
Background: Capitellar osteochondritis dissecans (OCD) in skeletally immature athletes has often been seen in baseball players and gymnasts. The choice of surgical procedure for unstable lesions in skeletally immature athletes remains controversial. Purpose: To investigate functional outcomes and radiographic changes in the midterm to long-term postoperative period after arthroscopic (AS) resection for small to large capitellar OCD lesions in skeletally immature athletes. Study Design: Case series; Level of evidence, 4. Methods: A total of 38 elbows in 38 patients (33 boys, 5 girls; mean age, 14 years [range, 13-15 years]) with skeletally immature elbows underwent AS resection for capitellar OCD. Patients were observed for at least 5 years (mean, 8 years [range, 5-12 years]). Elbows with a lesion width that did not exceed one-half of the radial head diameter were assigned to group 1 (n = 17 elbows), and larger lesions were assigned to group 2 (n = 21 elbows). Functional scores, patient satisfaction, range of motion (ROM), and osteoarthritis (OA) grades were evaluated between the groups. Results: All patients returned to sports activity. Functional scores at the final follow-up were not significantly different between the groups. Patient satisfaction scores were significantly higher in group 1 than in group 2. There was significant improvement in flexion ROM at the final follow-up compared with preoperative values in group 1 ( P = .017), and there was a significant between-group difference (group 1: 141°; group 2: 133°; P = .002). Extension ROM showed significant improvement in both groups (group 1: from –8° to 3°; group 2: from –17° to –1°; P < .001 for both). Group 1 tended to have better extension than group 2, but the difference was not significant. There were no elbows with severe OA in either group, but the OA grade progressed in 5 elbows (29%) in group 1 and 9 elbows (43%) in group 2, and this rate of OA progression was statistically significant between groups ( P = .005). Conclusion: Both functional outcomes and radiological findings after AS fragment resection were excellent in elbows with small lesions. Although overall outcomes were acceptable in elbows with larger lesions, flexion ROM and patient satisfaction scores were significantly inferior to those in elbows with smaller lesions.